Faricimab efficacy in type 1 macular neovascularization: AI-assisted quantification of pigment epithelium detachment (PED) volume reduction over 12 months in Naïve and switch eyes - Jennifer Cattaneo; Paolo Forte; Giovanni Forte; Chiara M. Eandi (International Journal of Retina and Vitreous)
Abstract Background This study evaluates the efficacy of intravitreal Faricimab in reducing pigment epithelium detachment (PED) and fluid volumes in both treatment-naïve eyes and eyes unresponsive to anti-VEGF mono-therapies, all diagnosed with type 1 macular neovascularization (T1 MNV) over a period of 12-month. Methods A retrospective, single-center cohort study was conducted at the Jules Gonin Eye Hospital, Lausanne, Switzerland. Clinical records of treatment-naïve and non-responder switch patients presenting T1 MNV secondary to neovascular age-related macular degeneration (nAMD) from September 2022 to March 2023 were reviewed. Patients received a loading dose of three monthly Faricimab injections followed by a treat-and-extend (T&E) regimen. Multimodal imaging, including structural OCT and AI-assisted analysis, was used to quantify PED volumes and related fluid biomarkers at baseline, 3-month, 6-month, and 12-month follow-up. Statistical analyses included linear mixed models to evaluate differences and trends in intraretinal (IRF), subretinal fluid (SRF) and PED volumes. Results 65 eyes of 65 patients were enrolled (female: 70.7%; mean age = 80.7yrs, SD = 6.9yrs). 80% had received anti-VEGF treatment (Switch group) and 20% were treatment-Naïve at baseline. At 12 months, intravitreal treatments were more frequent in the Switch group (mean number = 8.3 vs. 6.0; p = 0.009). BCVA improved at the 12-month follow-up in Naïve eyes (+ 6.9 ETDRS letters from baseline, p = 0.053) and was maintained in Switch eyes. No cases of intraocular inflammation were observed. Significant reduction in SRF and IRF volumes were noted in both groups. A significant reduction in PED volume was observed over the follow-up period in both groups (mean slope = -206 nL, 95%CL = -273/-138; p-value < 0.001). Conclusions Intravitreal Faricimab significantly reduced PED volumes in both treatment-Naïve and non-responder Switch patients over 12 months. The study highlights Faricimab’s potential as an effective treatment option for T1 MNV in nAMD, offering significant improvements in PED volume and related fluid biomarkers.